Case Study : Development of POSYANDU (Pos Pelayanan Terpadu) Information System - Wiyono, Slamet; Wibowo, Dega Surono; Bachtiar, M. Yusuf (Politeknik Ganesha Medan, 2019)
Data management and information dissemination of Posyandu in Wanasari village, Brebes Regency is done manually. Data management is done by recording data into books, and the information is disseminated through oral. This method is not efficient because it causes difficulties in processing data and information of Posyandu. To overcome this problem, a website information system was created with exploiting the SMS (short message service). The website is used to display posyandu participant data or information, while the SMS gateway is used to send messages automatically to participants. The test results using the black-box method have not found a problem. Thus the Posyandu Information System is made ready to be tested on the community of Wanasari village, Brebes Regency.